HUBUNGAN PEMBERIAN ASI TERHADAP KEJADIAN STUNTING PADA BALITA USIA 2-5 TAHUN DI PUSKESMAS MANGGAR BARU, BALIKPAPAN PERIODE JULI-AGUSTUS 2019 - Louisa A. Langi; Regina Agape C. Toding (Jurnal Pro-Life, 2020)
The number of children currently suffering from stunting globally is 150.8 million, so stunting has become a globalhealth problem. According to WHO (World Health Organization) the average prevalence of stunted children inIndonesia on 2005-2017 was 36.4% and especially in East Kalimantan, the prevalence of stunted children was24%. Along with this problem, a nutritional improvement movement was made focusing on 1000 HPK and carriedout globally, named the Scaling Up Nutrition (SUN) Movement with one of the main target is breastfeedingmothers. For this reason, this study aims to determine the relationship of breastfeeding to stunting at the ManggarBaru Health Center with a cross-sectional research design. Data is collected using a questionnaire that has beentested for validity and reliability as well as by anthropometric measurements of children 2-5 years. As a result,27 out of 47 children (57.4%) experienced stunting and of those stunted children there were 11 children notbreastfed until 2 years of age. There was a significant relationship between breastfeeding to children for 2 yearswith stunting (p =0,021).Keywords: breastfeeding, stunted children